2019
DOI: 10.1039/c8sm02507j
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic probing of the complex interfacial rheology of multilayer capsules

Abstract: Encapsulation of chemicals using polymer membranes enables to control their transport and delivery for applications such as agrochemistry or detergency. To rationalize the design of polymer capsules, it is necessary to understand how the membranes' mechanical properties control the transport and release of the cargo. In this article, we use microfluidics to produce model polymer capsules and study in situ their behavior in controlled elongational flows. Our model capsules are obtained by assembling polymer mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In many biologically and industrially relevant applications, finite-size effects become crucial for an accurate and reliable description of transport processes ranging from the microscale to the nanoscale. Prime examples include the ionic transport and electrokinetics in small-scale capacitors (Marini Bettolo (Daiguji et al 2004), and the rheology of droplets, capsules or cells in constricted/structured microchannels (Park & Dimitrakopoulos 2013;Le Goff et al 2017;Trégouët et al 2018Trégouët et al , 2019, where boundary effects may play a pivotal role.…”
Section: Introductionmentioning
confidence: 99%
“…In many biologically and industrially relevant applications, finite-size effects become crucial for an accurate and reliable description of transport processes ranging from the microscale to the nanoscale. Prime examples include the ionic transport and electrokinetics in small-scale capacitors (Marini Bettolo (Daiguji et al 2004), and the rheology of droplets, capsules or cells in constricted/structured microchannels (Park & Dimitrakopoulos 2013;Le Goff et al 2017;Trégouët et al 2018Trégouët et al , 2019, where boundary effects may play a pivotal role.…”
Section: Introductionmentioning
confidence: 99%
“…For protein-stabilized emulsions, it is generally assumed that the formation of the interfacial layer structure takes place in time ranges between minutes and days. In previous studies, authors investigated interfacial rheology using microfluidics at time intervals up to hours, and found considerable differences in interfacial rheology [ 86 , 87 , 88 ]. However, a very recent study showed that the onset of these processes can already be detected at sub-second time scales [ 89 ].…”
Section: On-chip Analysis Of Food Dropletsmentioning
confidence: 99%
“…Furthermore, LbL-assembly method can only be utilized on water-soluble and charged polymer (polyelectrolyte) components, [40,41] and polymeric materials can be lost after each washing step, leading to uneven distribution between different layers. To address these issues, many modified techniques have been introduced, for instance, spin assembly, [42] spray assembly, [43,44] and fluidic assembly, [45,46] have been employed to speed up the coating procedure. To expand the types of compounds that could be used as LbL building blocks, an improved method that involves two steps of the assembly procedure was proposed.…”
Section: Layer-by-layer (Lbl) Self-assemblymentioning
confidence: 99%